Addressing Inconsistencies in the Social Norms Drinking Literature: Development of the Injunctive Norms Drinking and Abstaining Behaviors Questionnaire. (12th September 2016) - Meisel, Samuel N.; Colder, Craig R.; Read, Jennifer P.
Abstract : Background: Informed by inconsistent findings regarding the association between injunctive norms (IN) and drinking behaviors, the current study developed a new measure of IN, the Injunctive Norms Drinking and Abstaining Behaviors Questionnaire (IN‐DABQ). This measure addressed several psychometric weaknesses of prior assessment of this construct, specifically, reliance on single‐item measures, and assessment of a limited range of drinking behaviors. The new measure also assessed norms for reasons for abstaining from drinking as college students often have simultaneous motives to use and inhibit their drug use. A parallel measure of descriptive norms (DN), the Descriptive Norms Drinking and Abstaining Behaviors Questionnaire (DN‐DABQ), was created to allow for a comparison of the relative predictive effects of descriptive and IN in relation to different drinking outcomes. Methods: A college sample ( N  = 254, female = 50.42%) was recruited using Amazon's Mechanical Turk. Participants completed an online survey assessing demographic characteristics, social norms for 3 referents, weekly alcohol use, and alcohol‐related consequences. Results: Exploratory factor analyses indicated 2 factors for the DN‐DABQ and 3 factors for the IN‐DABQ. The IN Drinking Behaviors factor consistently predicted weekly consumption and alcohol‐related consequences across 3 reference groups (typical college student at your school, friends, and closest friends). Conclusions: These findings suggest that prior inconsistencies in the relationship between IN and drinking behaviors are likely a function of poor measurement of this construct. Implications for normative feedback interventions are discussed. Abstract : Motivated by inconsistent associations between injunctive norms (INs) and drinking outcomes, this study developed a new measure of INs (the IN Drinking and Abstaining Behaviors Questionnaire) that addressed psychometric weaknesses of prior measures. Analysis supported a three‐factor solution and the IN Drinking Behaviors factor consistently predicted drinking outcomes across three referents. Findings suggest that prior inconsistencies in the relationship between INs and drinking are attributable to poor measurement of INs and that INs are a robust correlate of drinking.